Anästhesie- und Intensivbeatmungsgeräte: Unterschiede und Nutzbarkeit bei COVID-19-Patienten - Notz, Q. (Anaesthesist, 2020)
The current coronavirus disease 2019 (Covid-19) pandemia is a highly dynamic situation characterized by therapeutic and logistic uncertainties. Depending on the effectiveness of social distancing, a shortage of intensive care respirators must be expected. Concomitantly, many physicians and nursing staff are unaware of the capabilities of alternative types of ventilators, hence being unsure if they can be used in intensive care patients. Intensive care respirators were specifically developed for the use in patients with pathological lung mechanics. Nevertheless, modern anesthesia machines offer similar technical capabilities including a number of different modes. However, conceptual differences must be accounted for, requiring close monitoring and the presence of trained personnel. Modern transport ventilators are mainly for bridging purposes as they can only be used with 100% oxygen in contaminated surroundings. Unconventional methods, such as „ventilator-splitting“, which have recently received increasing attention on social media, cannot be recommended. This review intends to provide an overview of the conceptual and technical differences of different types of mechanical ventilators.